Vidas que no son las nuestras. Obra y crítica en tránsito entre culturas en Las brutas de Rafael Díaz y Las niñas Quispe de Sebastián Sepúlveda - Martina Bortignon (Confluenze, 2019)
This paper will discuss a movie and a multimedia work based on the play Las brutas by Juan Radrigán, about the last days of three Colla shepherds, who lived isolated in the northern Chilean Andes. Western and urban projections about the relation between human being and environment and the meaning of life that are on display in the works will be explored. Through the interplay among Colla ethnological sources, Andean thought and phenomenology, the paper aims at problematizing the very premises of critical approach.